Diagnostic Accuracy of Magnetic Resonance Imaging in Diagnosing ACL Injuries Taking Arthroscopy as Gold Standard - Muhammad Afaq, Amaar Talib, Rukhsana Nasim, Khalid Javed, Hira Ashfaq Butt, Fareeha Shahid, Islah Uddin, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Low velocity, non - intrusive, acceleration-deceleration, and contact traumas with a rotating component are the most common causes of anterior cruciate ligament (ACL) injuries. The objective of the study was: To determine the diagnostic accuracy of magnetic resonance imaging in detecting anterior cruciate ligament tear using arthroscopy as a gold standard.” Materials and methods: MRI scans of all the cases performed in the hospital radiology department and reported by a radiologist for ACL tear. Arthroscopy reports which were performed under general anesthesia by a senior orthopedic surgeon were also reviewed. ACL tear was assessed as an operational definition. Whole data was collected and recorded on an already structured Performa Results: Arthroscopy confirmed anterior cruciate ligament tear in 78 (62.40%) cases whereas 47 (37.60%) patients revealed no anterior cruciate ligament tear. In MRI-positive patients, 72 (True Positive) had an anterior cruciate ligament tear and 06 (False Positive) had no anterior cruciate ligament tear on arthroscopy. Among, 47 MRI negative patients, 06 (False Negative) had anterior cruciate ligament tear on arthroscopy whereas 41 (True Negative) had no anterior cruciate ligament tear on arthroscopy Conclusion: This study concluded that magnetic resonance imaging has high sensitivity and accurate modality, which has not only dramatically enhanced our tendency to diagnose anterior cruciate ligament injury but also helpful in reducing the number of pure diagnostic arthroscopies. So, we recommend that preoperative MRI should be done in every patient with ACL injury for selecting proper therapy for these particular patients. Keywords: Trauma, Anterior cruciate ligament (ACL) injuries, MRI, Arthroscopy, Diagnostic Accuracy